2018
DOI: 10.7554/elife.35656
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic-dependent glutamatergic neurotransmission from kisspeptin neurons governs feeding circuits in females

Abstract: The neuropeptides tachykinin2 (Tac2) and kisspeptin (Kiss1) in hypothalamic arcuate nucleus Kiss1 (Kiss1ARH) neurons are essential for pulsatile release of GnRH and reproduction. Since 17β-estradiol (E2) decreases Kiss1 and Tac2 mRNA expression in Kiss1ARH neurons, the role of Kiss1ARH neurons during E2-driven anorexigenic states and their coordination of POMC and NPY/AgRP feeding circuits have been largely ignored. Presently, we show that E2 augmented the excitability of Kiss1ARH neurons by amplifying Cacna1g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
140
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(149 citation statements)
references
References 87 publications
9
140
0
Order By: Relevance
“…While the effects of E2 and ghrelin in ARC KNDy neurons have become more defined, it is critical to keep in mind that KNDy neurons are one node of a large circuit within the ARC. KNDy neurons not only project locally to POMC and NPY neurons but also to preoptic GnRH and kisspeptin neurons of the AVPV, playing an important role in puberty and ovarian functions [37,47]. KNDy neurons activate POMC neurons via kisspeptin and glutamate release and inhibit NPY neurons directly via glutamate and indirectly through kisspeptin [16,37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the effects of E2 and ghrelin in ARC KNDy neurons have become more defined, it is critical to keep in mind that KNDy neurons are one node of a large circuit within the ARC. KNDy neurons not only project locally to POMC and NPY neurons but also to preoptic GnRH and kisspeptin neurons of the AVPV, playing an important role in puberty and ovarian functions [37,47]. KNDy neurons activate POMC neurons via kisspeptin and glutamate release and inhibit NPY neurons directly via glutamate and indirectly through kisspeptin [16,37].…”
Section: Discussionmentioning
confidence: 99%
“…KNDy neurons not only project locally to POMC and NPY neurons but also to preoptic GnRH and kisspeptin neurons of the AVPV, playing an important role in puberty and ovarian functions [37,47]. KNDy neurons activate POMC neurons via kisspeptin and glutamate release and inhibit NPY neurons directly via glutamate and indirectly through kisspeptin [16,37]. As all 3 neurons modulate the excitability of the other 2 neuronal populations and respond differently to peripheral peptide hormones, any modulation of one neuronal population by a hormone will have disparate effects on the other 2 popu-…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that some degree of reciprocal communication occurs between the ARN KISS and AgRP/NPY neurones. An early brain slice study reported that kisspeptin inhibited the firing of AgRP/NPY neurones in an indirect manner, 36 whereas another found evidence for a direct glutamatergic input from ARN KISS neurones that would excite AgRP/NPY neurones at low firing rates but inhibit their activity at higher frequencies through group II metabotropic glutamatergic receptors 37,38 . Thus, directly or indirectly, ARN KISS neurones are able to suppress the activity of AgRP/NPY neurones.…”
Section: Discussionmentioning
confidence: 99%